Integrating Behavior Driven Testing Approach with Cypress and Cucumber - Abdullah; Muhammad Usman; Najeeb Ullah (VFAST Transactions on Software Engineering, 2025)
Software testing is integral to ensuring the functionality and quality of applications. This study highlights the implementation of Cypress and Node.js by the Nokia RON team to address the challenges of GUI testing. The adoption of Cypress enabled comprehensive and targeted testing, alongside efficient resolution of dependency and third-party package issues through selective installation. By integrating Cypress with Cucumber, an easy-to-use interface was developed to transform smoke test checklists into Gherkin syntax, enhancing readability and adaptability. Additionally, the use of Mochawesome Reporter provided detailed HTML reports, facilitating issue tracking and quick resolutions. This methodology, supported by a structured questionnaire, fostered stakeholder satisfaction and collaboration, resulting in an interactive and effective testing environment. The findings emphasize the role of Behavior Driven Development (BDD) in streamlining automated testing, improving communication among stakeholders, and ensuring higher software quality.